45=(y+6)(y-6)

Rewrite the equation as (y+6)(y-6)=45.

(y+6)(y-6)=45

Expand (y+6)(y-6) using the FOIL Method.

Apply the distributive property.

y(y-6)+6(y-6)=45

Apply the distributive property.

y⋅y+y⋅-6+6(y-6)=45

Apply the distributive property.

y⋅y+y⋅-6+6y+6⋅-6=45

y⋅y+y⋅-6+6y+6⋅-6=45

Simplify terms.

Combine the opposite terms in y⋅y+y⋅-6+6y+6⋅-6.

Reorder the factors in the terms y⋅-6 and 6y.

y⋅y-6y+6y+6⋅-6=45

Add -6y and 6y.

y⋅y+0+6⋅-6=45

Add y⋅y and 0.

y⋅y+6⋅-6=45

y⋅y+6⋅-6=45

Simplify each term.

Multiply y by y.

y2+6⋅-6=45

Multiply 6 by -6.

y2-36=45

y2-36=45

y2-36=45

y2-36=45

Add 36 to both sides of the equation.

y2=45+36

Add 45 and 36.

y2=81

y2=81

Take the square root of both sides of the equation to eliminate the exponent on the left side.

y=±81

Simplify the right side of the equation.

Rewrite 81 as 92.

y=±92

Pull terms out from under the radical, assuming positive real numbers.

y=±9

y=±9

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

y=9

Next, use the negative value of the ± to find the second solution.

y=-9

The complete solution is the result of both the positive and negative portions of the solution.

y=9,-9

y=9,-9

y=9,-9

Solve for y 45=(y+6)(y-6)